"أثر استخدام المنصة التعليمية Google Classroom في تحصيل طلاب الصف الثالث المتوسط لمادة الجغرافية في ظل جائحة كورونا" (Journal of the College of Basic Education, 2022)
The aim of the research is to investigate the effect of using the Google Classroom educational platform on the achievement of third-grade intermediate students of geography within the spread of the Corona pandemic, and the research sample consisted of (80) students of the third intermediate grade enrolled in the first semester of the academic year (2020/2021) by (40) One student for the experimental group, who studied using the educational platform, and (40) students for the control group, who studied in the traditional method. The researchers used the quasi-experimental approach, the researchers prepared the research tool represented by the achievement test consisting of (20) items in its final form, and the validity and reliability of the tool was confirmed, which reached (0.84), After completing the data collection, the statistical analysis was done by using the (SPSS) program, and the results resulted in statistically significant differences at the level of significance (a <0.05) between the arithmetic averages of the grades of middle third grade students in the geography subject in achievement attributable to the Google Classroom educational platform variable Within the period of the spread of the Corona pandemic, among the members of the experimental group and the control group in the achievement test, and for the benefit of the experimental group, the researchers recommended several recommendations, the most important of which is the development of digital skills in the field of using educational platforms in teaching social sciences by conducting workshops and training courses and directing social sciences teachers to use Educational platforms, including Google Classroom, in their teaching, which has an impact on student achievement.